1999
DOI: 10.1679/aohc.62.441
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Localization of Taurine in the Developing Retina of the Lofteye Flounder Paralichthys olivaceus.

Abstract: Light microscopic immunolocalization of taurine, a sulfur-containing free amino acid, was investigated in the developing retina of a lefteye flounder, Paralichthys olivaceus, which exhibits metamorphic changes with rod cell addition for 3-5 weeks after hatching. This immunocytochemical study of the developing retina revealed: 1) From 3 to 13 days after hatching, intense immunostaining was shifted from the surroundings of neural cells to the neural somata and processes in the inner retina. 2) Intense immunoreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…We compared the ratio of rod nuclei versus cone ellipsoids, and the number of rod outer and inner segment layers, in the elver from the coastal sea, adults from the river, and migrating adults from the ocean. This result was in agreement with our previous findings in the lefteye flounder Paralichthys olivaceus 12,17 . In the flounder, a pure‐cone retina exists until 2 or 3 weeks after hatching, rods appear at around 40 days at metamorphosis, and the adult retina has a single layer of cones and pseudo‐multilayered bank of rod outer and inner segments 12,17 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We compared the ratio of rod nuclei versus cone ellipsoids, and the number of rod outer and inner segment layers, in the elver from the coastal sea, adults from the river, and migrating adults from the ocean. This result was in agreement with our previous findings in the lefteye flounder Paralichthys olivaceus 12,17 . In the flounder, a pure‐cone retina exists until 2 or 3 weeks after hatching, rods appear at around 40 days at metamorphosis, and the adult retina has a single layer of cones and pseudo‐multilayered bank of rod outer and inner segments 12,17 .…”
Section: Discussionsupporting
confidence: 91%
“…This result was in agreement with our previous findings in the lefteye flounder Paralichthys olivaceus 12,17 . In the flounder, a pure‐cone retina exists until 2 or 3 weeks after hatching, rods appear at around 40 days at metamorphosis, and the adult retina has a single layer of cones and pseudo‐multilayered bank of rod outer and inner segments 12,17 . Generally, retinal modifications for increasing sensitivity are found in deep‐sea fishes: 18 multibank of rods, by increasing the number of photoreceptors within a given area, are thought to enhance sensitivity 10,18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Taurine is a major osmolyte in marine fish and invertebrates and the importance of taurine as an organic osmolyte varies with species 2 . Omura and Yoshimura 18 suggested that the abundant taurine localization in the retinal photoreceptor and neural layers of juvenile flounder may be involved in the protection of the photoreceptor outer segment, the regulation of neural transmission, and photoreceptor differentiation during the developmental stages. Taurine has an important role in the osmotic stabilization of neurons in the retina and brain of juvenile flounder 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Species lacking sufficient endogenous synthesis require dietary supplementation. As in mammals, taurine plays important roles in many physiological processes in fish including bile salt conjugation [18], osmoregulation [19], and vision [20,21]. In addition, dietary taurine supplementation has been shown to stimulate growth in multiple fish species, such as rainbow trout [22]; Japanese flounder [18,23]; turbot [24]; red seabream [25,26]; cobia [27,28,29,30,31]; Atlantic salmon [32]; and yellowtail [33].…”
Section: Introductionmentioning
confidence: 99%